The Iron Curtain: Macrophages at the Interface of Systemic and Microenvironmental Iron Metabolism and Immune Response in Cancer - DeRosa, Angela; Leftin, Avigdor (Frontiers in Immunology, 2021)
Macrophages fulfill central functions in systemic iron metabolism and immune response. Infiltration and polarization of macrophages in the tumor microenvironment is associated with differential cancer prognosis. Distinct metabolic iron and immune phenotypes in tumor associated macrophages have been observed in most cancers. While this prompts the hypothesis that macroenvironmental manifestations of dysfunctional iron metabolism have direct associations with microenvironmental tumor immune response, these functional connections are still emerging. We review our current understanding of the role of macrophages in systemic and microenvironmental immune response and iron metabolism and discuss these functions in the context of cancer and immunometabolic precision therapy approaches. Accumulation of tumor associated macrophages with distinct iron pathologies at the invasive tumor front suggests an “Iron Curtain” presenting as an innate functional interface between systemic and microenvironmental iron metabolism and immune response that can be harnessed therapeutically to further our goal of treating and eliminating cancer.